Essays on corruption and governance - Toukan, Amjad (2007)
Nearly 2500 years ago, the old Indian treatise entitled "Arthashastra" had recognized the impact of corruption on the conduct of the economy. Corruption is not just an economic problem, however; it is also associated with bad governance (governance being defined as the way in which both public and private institutions perform their functions in a country). In my dissertation, I focus on the principal-agent model of corruption. The agency relationship links at least two actors and is the basic unit of analysis. The first chapter evaluates a corporation's decision to go public, draws the distinction between large and dispersed shareholders and examines how the differences in their incentives to monitor the managers affect the shape of ownership structure in public firms. In the second chapter, I find evidence contradicting the predictions of the Rybczynski theorem using a sample of 28 manufacturing industries in 16 developing countries over eight years. This contradiction is examined using a modification of the Heckscher-Ohlin model to allow for international variability in corruption and risk of expropriation. The final chapter explores the properties and implications of a general class of "difference-form" contests that has been derived for settings in which rent-seeking involves persuasion. Such class of contests could be employed to analyze the impact of corruption in governance such as the decision-making in the courtroom, the decision making within bureaucracies, the interactions among interest groups among others.